4CPS-206 Impact of pharmaceutical interventions in parenteral nutrition. (March 2019) - Brito, M; Alcobia, A
Abstract : Background: The role of pharmacists in parenteral nutrition (PN) management differs between hospitals. In our case, pharmacists are not limited to PN compounding and distribution. For instance, for more than 20 years, pharmacists have been supporting the calculation of patients' basal metabolism (PBM) and developed protocols for a gradual introduction of PN in order to avoid refeeding syndrome (RS). Purpose: To evaluate pharmaceutical interventions (PI) in PN, its acceptance and impact. Material and methods: Prospective study including patients on PN, March to September 2018. Data were collected through communication with nurses/physicians or from electronic records. Prescriptions were electronically validated daily. PBM was calculated by the Harris–Benedict formula. All interventions and relevant clinical data were recorded and analysed. Results: The study included 69 patients (65.5±16.6 years; 68.1% males). There were 66 PI in 126 prescriptions (52.3%), with an acceptance rate of 90.2%. PBM and rate infusion calculation represented 54.5% of all PI. Suggestions for special protocols due to the high risk of RS were 3.3% of PI. During the study, only one patient developed RS. The main prescription error was incorrect NP bag selection so consequently, 18.4% of PI were prescribed bag adjustments. Alerts to physician NP electronic prescription discontinuation represented 9.8% of PI. In 2016–2017, the waste in supplemented bags with expired date resulted in a loss of €526/year on average. The reason for this waste was verbal NP discontinuation. These alerts, together with a better communication with nursing teams, resulted in zero waste. Other PI were: electrolytic imbalances corrections (5.4%), scheduling of NP suspension days (4.3%), hydric imbalances adjustments (2.2%) and correction of prescribed lipid supplements (2.2%). All standard bags were supplemented in a laminar flow chamber. Only one patient presented central venous catheter (CVC) infection with positive blood culture. In the homologous period of 2013–2014, when the bags were supplemented in the wards, the number of CVC infections was six. Conclusion: Pharmacists are key elements with a recognised value of their interventions (90.2% acceptance rate) which improved the adequacy and safety of PN concerning metabolic- and catheter-related complications. Reference and/or acknowledgements: Giancarelli A, Davanos E. Evaluation of nutrition support pharmacist interventions. JPEN 2014;39:476–81. Available from https://www.ncbi.nlm.nih.gov/pubmed/25303948 No conflict of interest.